Comparison of Efficacy of Fosfomycin and Ceftriaxone in the Treatment of Urinary Tract Infections in Children (Medical Forum Monthly, 2024)
Objective: To compare the efficacy of oral Fosfomycin and Intravenous ceftriaxone in the treatment of urinary tract infections (UTIs) in children upto 16 years of age.Study Design: Randomized Clinical Trial (RCT)Place and Duration of Study: This study was conducted at the Department Pediatrics, MTI HMC Peshawar from November 2016 to April 2017.Materials and Methods: 390 children with UTI were randomly allocated in two groups A (195) to receive fosfomycin and B (195) to receive ceftriaxone. Urine culture was done at the 5th day of the start of therapy to determine the effect of drug.Results: We found the mean age group of our whole sample was 9.4 ± 2.3 years. The mean age of children in group A was 9.4 ± 2.4 years while in group B it was 9.3 ± 2.2 years (p 0.949). There were 61.5% males in group A compared to 67.7% in group B (p 0.204). On follow up, repeat urine culture was performed in all children and it was observed that 72.3% children in fosfomycin group and 60% children in ceftriaxone group were having negative urine culture (efficacy) p 0.01.Conclusion: Fosfomycin is effective compared to ceftriaxone in the treatment of UTIs (urinary tract infections) in children.